1995
DOI: 10.1021/ac00119a016
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Amino Aromatics for Solid-Phase Detection Using Imidazole-Mediated Bis(trichlorophenyl) Oxalate Chemiluminescence

Abstract: This investigation examines six amino polycyclic aromatic hydrocarbons, covalently immobilized onto nonporous and porous methacrylate, controlled-pore glass, and Mer-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…The amount of accessible glycidyl groups was stated by the manufacturer to be 0.3 ± 0.1 mmol/g for this particular batch; however, in a previous report we found that only approximately 40 µmole/g of amino-PAH could be immobilized on this support [22]. No further modification was done prior to immobilization.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…The amount of accessible glycidyl groups was stated by the manufacturer to be 0.3 ± 0.1 mmol/g for this particular batch; however, in a previous report we found that only approximately 40 µmole/g of amino-PAH could be immobilized on this support [22]. No further modification was done prior to immobilization.…”
Section: Methodsmentioning
confidence: 73%
“…No further modification was done prior to immobilization. Controlled pore glass PG350-400 (200-400 mesh, 37-74 µm) was epoxidated with (3-glycidoxypropyl)trimethoxysilane (GLYMO, Merck) as described previously [3,22]. The dry state nitrogen adsorption BET surface area was specified by the manufacturer, Sigma (St. Louis, MO), to be 95 m 2 /g, however our measurements (Chalmers Institute of Technology, Gothenburg) estimated the surface area to be 77 ± 1.8 m 2 /g (n = 4), which was later verified by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the dramatic enhancement of CL intensity as shown in Experiment 6 (comparing with and without cotton) in Table 1, it is possible that the entanglement of the surfactant aggregates with the filtering material may also contribute in part to an overall enhancement in the observed CL intensity, due to an increase in the CL efficiency and/or rate of reaction for the detection of bilirubin using the nitrite-hydrogen peroxide CL system. It should also be mentioned that the measurements of CL in solid phase media usually involve the immobilization (i.e., chemical attachment) of the analyte or CL reagents onto the solid substrate [25]. The physical entrapment of analyte-containing surfactant aggregates inside a cotton-filled collection column as demonstrated in the present work therefore represented a novel approach by which heterogeneous CL measurements can be carried out.…”
Section: Enhancement Factormentioning
confidence: 91%
“…Although CL enhancement effects have been reported in micellar solutions [24] as well as certain kinds of solid materials [21,25,26] (e.g., glass fiber filter, cellulose filter, synthetic polymers, etc.) for various analytes, the possible enhancement of CL intensity due to the effect of a mixture of highly viscous surfactant aggregates and solid filtering material (e.g., cotton, glass wool or nylon fiber) has not been reported.…”
Section: Enhancement Factormentioning
confidence: 99%